Early Onset Intrauterine Growth Restriction in a Mouse Model of Gestational Hypercholesterolemia and Atherosclerosis. (10th September 2014) - Busso, Dolores; Mascareño, Lilian; Salas, Francisca; Berkowitz, Loni; Santander, Nicolás; Quiroz, Alonso; Amigo, Ludwig; Valdés, Gloria; Rigotti, Attilio
Abstract : The susceptibility to develop atherosclerosis is increased by intrauterine growth restriction and prenatal exposure to maternal hypercholesterolemia. Here, we studied whether mouse gestational hypercholesterolemia and atherosclerosis affected fetal development and growth at different stages of gestation. Female LDLR KO mice fed a proatherogenic, high cholesterol (HC) diet for 3 weeks before conception and during pregnancy exhibited a significant increase in non-HDL cholesterol and developed atherosclerosis. At embryonic days 12.5 (E12.5), E15.5, and E18.5, maternal gestational hypercholesterolemia and atherosclerosis were associated to a 22–24% reduction in male and female fetal weight without alterations in fetal number/litter or morphology nor placental weight or structure. Feeding the HC diet exclusively at the periconceptional period did not alter fetal growth, suggesting that maternal hypercholesterolemia affected fetal weight only after implantation. Vitamin E supplementation (1, 000 UI of α-tocopherol/kg) of HC-fed females did not change the mean weight of E18.5 fetuses but reduced the percentage of fetuses exhibiting body weights below the 10th percentile of weight (HC: 90% vs. HC/VitE: 68%). In conclusion, our results showed that maternal gestational hypercholesterolemia and atherosclerosis in mice were associated to early onset fetal growth restriction and that dietary vitamin E supplementation had a beneficial impact on this condition.